The Legal Discourse of Al-Ādah Muhakkamah on Mappanini Bosi Tradition in Bone Regency - Widjaja, Abdi; Mahmusin, Muhammad Arash bin; Abdulrazak, Fahri Asyudi; Nazaruddin, Rezkiawati (Mazahibuna: Jurnal Perbandingan Mazhab, 2023)
The inhabitants of Pattiro Village, situated within the Dua Boccoe Subdistrict of Bone Regency, are renowned for their customary practice known as "mappanini bosi." However, it has been observed that adherence to the established rules of this tradition is frequently breached by community members. This research aims to explore the use of mappanini bosi tradition within Bugis society and to examine perspective of Islamic law on the jurisprudential rule of al-ādah muhakkamah. Accordingly, this empirical qualitative research was conducted in Pattiro Village, situated within the Salomekko District of Bone Regency in South Sulawesi Province. The methodology used adopted a synthesis of two theoretical frameworks, namely the reception-exit theory and al-'urf. To achieve the research aim, data were gathered through field studies and literary sources, and subsequently processed and analyzed using reduction, presentation, and conclusion methods. The obtained results showed the significance of mappanini bosi tradition within Bugis community, which was recognized as integral for achieving success in their various endeavors. It was also observed that not all individuals in Pattiro Village actively engage in this custom. Ritual stages of mappanini bosi include the use of leaves, millipede animals, sharpening stones, burning dippers, and underwear. In accordance with this, the fiqh rule al-ādah muhakkamah concerning the practice of mappanini bosi was evaluated in this research. From this evaluation, it was found that some elements deviated from certain Muslim beliefs, but not all aspects contravened mappanini bosi principles. Ritual process comprised the use of specific materials, and intentions, and attributing significance to ritual items believed to influence rainfall. This research urges practitioners of rain-charming ritual and Bugis community to regard mappanini bosi as local wisdom while concurrently respecting Islamic law as an integral component of community life.